Association between comorbidity and survival in head and neck cancer: Results from Head and Neck 5000. Issue 4 (14th December 2018) - Schimansky, Sarah; Lang, Samantha; Beynon, Rhona; Penfold, Christopher; Davies, Amy; Waylen, Andrea; Thomas, Steve; Pring, Miranda; Pawlita, Michael; Waterboer, Tim; Ness, Andy
Abstract: Background: People with head and neck cancer have higher comorbidity levels but it remains unclear if pretreatment comorbidity is an independent prognosticator in head and neck cancer. Methods: Survival analyses were performed using data from participants in a UK multicentre cohort study with cancers of the oral cavity ( n = 668), oropharynx ( n = 1074), and larynx ( n = 530). Survival analyses were incrementally adjusted for age, sex, marital status, income, education, stage, alcohol, and smoking. Results: After adjusting for demographic, clinical, and behavioral confounders, higher baseline comorbidity was associated with reduced overall survival (mild comorbidity HR = 1.4, 95% CI = 1.1, 1.7; moderate comorbidity HR = 1.7, 95% CI = 1.3, 2.2; severe comorbidity HR = 2.8, 95% CI = 1.9, 4.; P ‐trend<.001). Conclusions: Our findings suggest that comorbidity is an independent prognosticator for overall survival in head and neck cancer. Comorbid illnesses should be considered in the assessment and treatment planning of people with head and neck cancer.